Patients with Congestive Cardiac Failure Referred to Specialist Palliative Care. (April 2023) - Walsh, Maria; Kiely, Fiona
Background: Congestive cardiac failure is a chronic, progressive condition with a significant symptom burden. There is limited data available regarding the palliative care requirements of the heart failure population. Aims: To characterise patients with a primary diagnosis of congestive cardiac failure referred to a specialist palliative care (SPC) service in Ireland. Methods: A retrospective chart review of patients with congestive cardiac failure admitted to the specialist palliative care unit or reviewed by the community palliative care team over 2 years was carried out, utilising a data collection template. Results: 57 patient charts were included. 54% (n = 31) were female. Mean age was 81 [60 - 97] years. GP's referred 42% (n = 24), Cardiologists 39% (n = 22) and other hospital consultants 19% (n = 11). The commonest symptom reported was dyspnoea (n = 47). Time from referral to death ranged from less than one month (n =22) to greater than one year (n = 3). 14 patients were discharged from the service due to lack of SPC needs. Place of death was distributed between home, hospice, nursing home and acute hospital. Conclusions: Patients with congestive cardiac failure experience high symptom burden. More than 50% of patients that died while receiving SPC input had been referred less than 1 month prior, while almost a quarter of all referrals resulted in patient discharge. This highlights the importance of further education regarding indication for specialist palliative care referral and the benefits of early referral in this patient cohort when appropriate.